ΜΟΡΦΕΣ «ΑΜΦΙΧΡΟΝΙΑΣ» ΣΤΙΣ ΣΥΓΧΡΟΝΕΣ ΠΑΡΑΣΤΑΣΕΙΣ ΤΩΝ ΤΡΩΑΔΩΝ ΤΟΥ ΕΥΡΙΠΙΔΗ [TEMPORAL OVERLAPS IN MODERN PERFORMANCES OF EURIPIDES’ TROADES] - Briakou , Eirini-Niki (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
Euripides’ Troades remains one of the most popular tragedies performed in the modern stage. The significant impact of the play lies primarily in its timeless anti-war character and Euripides’ ability to shorten the temporal gap between Trojan Women’s reality and the historical and socio-political context of the 5th century BCE, attempting thus to elicit an emotional and mental «awakening» of the theatre audience. This paper explores how modern performances continue to draw on Euripides’ approach building a strong connection between the past and the present. The study focuses on the means and techniques used by directors and stage designers that underline the relevant theme of the war and encourage contemporary spectators to engage with Troades’ anti-war message. The paper examines several recent 21st-century productions that blur the lines between past and present, achieving thus a kind of a «temporal overlap» (αμφιχρονία), including the performances directed by George Mouaimis (THOC, 2003), Nikaiti Kontouri (NTNG, 2009), Theodoros Terzopoulos (Attis Theatre, 2017) and Christos Sougaris (NTNG, 2023).